BUDGET OBLIGATIONS, ITS DEFINITION AND FEATURES - Шляхов, Ілля (Київський національний університет імені Тараса Шевченка, 2022)
The proposed article was prepared as part of a dissertation research on "Financial and Legal Regulation of Budget Obligations" in order to  determine the main features of the budget obligations as a financial and legal category, to differentiate the parties to such obligations for further scientific study of the grounds for budget commitments and their implementation. The research was conducted using a general scientific dialectical method of research. The primary special legal method of research used in the study is the method of legal hermeneutics, which consists of interpretation of legal texts. The author focuses on the genesis (formation) of the financial and legal category of the budget obligations. The relationship between the categories of "obligation" and "budgetary obligation", and its separation from the obligations in the nature of private law, is briefly covered. The problems of legal consolidation and definition of the concept of "budget obligations" and "budget financial obligations" are also studied. Attention is paid to the issue of systematization of budget legislation. The conclusions indicate possible ways to improve the legal consolidation of the concept of "budget obligations". The article describes in detail the key features of the budget obligations as a financial and legal category, arising from the provisions of budget legislation, namely the following features: 1) is public recognized, represented by the Treasury, the obligation to be paid from the budget; 2) corresponds to the budget allocation (carried out in accordance with it); 3) is subsequent, as it arises on the basis of the original obligation; 4) has a time frame corresponding to the budget period; 5) the parties to the budget obligation are the administrator of budget funds (recipient of budget funds) and the Treasury, as a body authorized by the state (territorial community, a legal representative of the owner). The problems of legal technique that takes place in the formulation of the Budget Code of Ukraine in terms of regulating budget commitments are considered. The general idea of the text is to discover the features of the concept "budget commitment" . It was defined by the author in great detail. Problems of the budget legislation connected with practical application of norms of the Budget code of Ukraine are highlighted. The author comes to the conclusion on future research of the issue of the need for a separate study on the grounds for budget commitments and their implementation.

Визначено основні ознаки бюджетного зобов'язання як фінансово-правової категорії, сторони такого зобов'язання задля подальшого наукового вивчення підстав виникнення бюджетних зобов'язань та їх виконання. Дослідження проводилось із застосуванням діалектичного методу. Основним спеціально-юридичним методом дослідження, що застосовувався в дослідженні, є метод юридичної герменевтики, який полягає в інтерпретації юридичних текстів. Приділено увагу генезису (становленню) фінансово-правової категорії бюджетного зобов'язання. Коротко висвітлено співвідношення категорій "зобов'язання" та "бюджетне зобов'язання", відмежування його від зобов'язань приватно-правового характеру. Також досліджено проблеми юридичного закріплення та визначення поняття "бюджетне зобов'язання". У висновках наведено можливі шляхи вдосконалення його правового закріплення. Детально та послідовно охарактеризовано ключові ознаки бюджетного зобов'язання як категорії фінансово-правової, що випливають із положень бюджетного законодавства. Виокремлено п'ять ключових ознак бюджетного зобов'язання, а саме: бюджетне зобов'язання 1) є публічним визнанням з боку органу Казначейства того, що його буде оплачено коштами бюджету; 2) відповідає бюджетному асигнуванню (здійснюється відповідно до нього); 3) є похідним, оскільки виникає на основі первинного зобов'язання; 4) має часові межі, що відповідають бюджетному періоду; 5) передбачає, що його сторонами є розпорядники (одержувачі) бюджетних коштів та орган Казначейства як уповноважений державою (територіальною громадою) орган (законний представник власника). Серед іншого розглянуто проблеми юридичної техніки, що виникають під час формулювання норм Бюджетного кодексу України в частині регулювання бюджетних зобов'язань. Автором порушено питання необхідності проведення окремого дослідження щодо підстав виникнення бюджетних зобов'язань та їх виконання.
БЮДЖЕТНЕ ЗОБОВ'ЯЗАННЯ, ЙОГО ПОНЯТТЯ ТА ОЗНАКИ
Keywords: фінансово-правове зобов'язання; бюджетне законодавство; казначейський контроль; виконання бюджетів; бюджетне зобов'язання; бюджетне фінансове зобов'язання; ознаки бюджетного зобов'язання; операції з бюджетними коштами; financial and legal obligations; budget legislation; treasury control; budget execution; budget obligations; budget financial obligations; features of budget obligations; operations with budget funds